Aquisição de linguagem: considerações sobre a relação língua materna e língua estrangeira - Malt, Samar Mohamad El (2012)
This paper is a reflection on mother tongue, subject that rarely has been object of attention in the field of Language Acquisition. We discuss what senses are under this syntagma, having as theoretical background the hypothesis that subjective structure and language structure are mutually determined, as pointed out by De Lemos (1992, 1995, 2000, 2002, among others). A discussion about the concept of Language and its effects, as proposed by Saussure (1916), in a proposal about language acquisition has also been considered. The reflection on the concept of Mother Tongue has also included issues related to the structuring of the subject and also the concept of lalangue, once the theoretical framework that guides this research is the one proposed by Cláudia De Lemos, who proposes a way to understand language acquisition from the effects approaching Jacques Lacan Psychoanalysis and the original understanding of European structuralism by that author. In this research we try to outline such concepts in the field of Linguistics and Psychoanalysis. We consider that from the treatment given in the field of Psychoanalysis we have brought up to discussion how it is treated inside Linguistics. Establishing a dialogue between these two areas allowed to conduct a reflection on what determines that a subject who is since early exposed to more than one language chooses the one that will be named Mother Tongue The starting point is the notion of subject constituted by language in the relation with the Other. The focus of this reflection have been the possible ways of relation of the subject with the mother Tongue and the foreign language. This study aimed to investigate the effects of the apparent deletion of one of the languages which turns a subject, or how these languages are interwoven in the structure of subjectivity. It is a subject that involves the relation subject-language-speech and that is relevant to reflect about language acquisition and its relation with Mother Tongue and Foreign Language